Employment‐Based, For‐Profit Health Care in a Pandemic - Kolmes, Sara (Hastings Cent Rep, 2020)
The emergence of Covid‐19 in the United States has revealed a critical weakness in the health care system in the United States. The majority of people in the nation receive health care via employment‐based health insurance from providers in a competitive market. However, neither employment‐based health care nor a competitive health care market can adequately provide treatment during a global pandemic. Employment‐based health care will fail to provide care for a large number of people in any destabilizing economic event, including a pandemic. Competitive for‐profit health care systems distribute limited goods based on markets rather than health care needs. If a global pandemic results in unusually high demand for specific medical supplies, then these will be distributed suboptimally. The combined risk of suboptimal distribution of needed goods and a significant drop in health care access in a global pandemic indicates that the U.S. health care system has serious vulnerabilities that need to be addressed.